Music and society in colonial Asunción: Comments on the book The singing Indians of Paraguay by Laura Fahrenkrog - Vera, Alejandro (2023)
The singing Indians of Paraguay: musical practices and dynamics of mobility in colonial Asunción (16th-18th centuries) (Buenos Aires: Editorial sb, 2020), written by musicologist and historian Laura Fahrenkrog, won the 2021 Clarence H. Haring Award » awarded by the American Historical Association every five years to a historical study on Latin America. In turn, the author's doctoral thesis, which gave rise to the book, obtained the Miguel Cruchaga Tocornal Award in 2018 from the Chilean Academy of History. Being very unlikely that a work with such distinctions is of low quality, it is not surprising that it is one of the most relevant investigations in recent years on the musical life of colonial Spanish America.